Heaven's Interpreters : Women Writers and Religious Agency in Nineteenth-Century America - Reed, Ashley, 1975-; Project Muse. (Ithaca [New York] : Cornell University Press, 2020)
"Heaven's Interpreters demonstrates how women writers of the American antebellum period used popular fictional genres to engage in theological debates and, in the process, brought into being new models of religious agency"--
Introduction : Writing Women's Religious Agency in Nineteenth-Century America -- "My Resolve is the Feminine of My Father's Oath" : Ritual Agency and Religious Language in the Early National Historical Novel -- "Unsheathe the Sword of a Strong, Unbending Will" : Sentimental Agency and the Doctrinal Work of Woman's Fiction -- "I Have Sinned against God and Myself" : Bearing Witness to Enslaved Women's Agency in Incidents in the Life of a Slave Girl -- "The Human Soul . . . Makes All Things Sacred" : Communal Agency in the Theological Romances of Harriet Beecher Stowe -- "I Have No Disbelief" : Women's Spiritualist Novels and Nonliberal Agencies -- Conclusion : Women's Religious Agency Today.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Fiction -- Religious aspects; Women and religion -- United States -- History -- 19th century; Women and literature -- United States -- History -- 19th century; Religion and literature -- United States -- History -- 19th century; American fiction -- 19th century -- History and criticism; American fiction -- Women authors -- History and criticism; United States -- Religion -- 19th century; Electronic books